2017
DOI: 10.1155/2017/7275109
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effect of Gemigliptin on Renal Injury in Murine Adriamycin-Induced Nephropathy

Abstract: Background. Previous studies have shown the antiapoptotic and anti-inflammatory potential of DPP-IV inhibitor in experimental models of renal injury. We tested whether DPP-IV inhibitor (gemigliptin) ameliorates renal injury by suppressing apoptosis, inflammation, and oxidative stress in mice with adriamycin nephropathy. Methods. Mice were treated with normal saline (control), gemigliptin (GM), adriamycin (ADR), or adriamycin combined with gemigliptin (ADR+GM). Apoptosis, inflammation, and oxidative stress were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In agreement with our findings, previous studies have shown that DPP-4 inhibitors have potent antiapoptotic effects in various types of cells [ 10 , 11 , 21 24 ]. In addition, DPP-4 inhibitors have been shown to protect against kidney damage induced by nephrotoxic insults, largely via inhibition of apoptosis [ 20 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our findings, previous studies have shown that DPP-4 inhibitors have potent antiapoptotic effects in various types of cells [ 10 , 11 , 21 24 ]. In addition, DPP-4 inhibitors have been shown to protect against kidney damage induced by nephrotoxic insults, largely via inhibition of apoptosis [ 20 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, a recent study showed that sitagliptin ameliorated NF- κ B activation and TNF- α production in doxorubicin-induced cardiotoxicity [ 23 ]. Moreover, accumulating evidence suggests that DPP-4 inhibitors exert anti-inflammatory effects in various organs, including the brain [ 21 ], liver [ 22 ], heart [ 24 ], and kidneys [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been argued whether DPP‐IV must be or must not be administered to cancer patients with diabetes, whereas other studies support the oral administration of DPP‐IV inhibitors in order to either enhance tumor immunotherapy or to slow the growth of different tumors or to suppress colorectal cancer lung metastases in mice . Other studies have demonstrated their therapeutic effects on obesity, neuropathy, and hepatic and renal pathologies. Recent studies have also shown that it is possible to design DPP‐IV inhibitors with dual bioactivity on other targets involved in cardiovascular diseases like ACE or β‐adrenergic receptors …”
Section: Introductionmentioning
confidence: 99%
“…12 In addition to the glucose-lowering effects of DPP-4 inhibitors and the tissue-protective effects of DPP-4 inhibition have been demonstrated in particular ischemia-reperfusion injury, diabetic kidney disease and CKD. Kim et al 13 reported that gemigliptin treatment led to a reduction in apoptosis, in ammation, and oxidative stress in a murine model of adriamycin-induced nephropathy. Choi et al 14 showed that gemigliptin attenuated cisplatin-induced renal dysfunction in mice.…”
Section: Discussionmentioning
confidence: 99%